"CONSTITUTIONAL TENDENCIES IN FORMING THE LEGAL AWARENESS OF YOUTH" (Western European Journal of Historical Events and Social Science, 2025)
This in the article in our country youth fold legal consciousness and literacy , youth constitution norms and the rules where at the level knowledge and him/her to life done increase potential about word goes